Characterization of pork bone soup odor active compounds from traditional clay and commercial electrical stewpots by sensory evaluation, gas chromatography–mass spectrometry/olfactometry and partial least squares regression. (24th August 2017) - Zhang, Man; Karangwa, Eric; Duhoranimana, Emmanuel; Zhang, Xiaoming; Xia, Shuqin; Yu, Jingyang; Xu, Man
Abstract: The effect of heating parameters on pork bone soup flavor generation in electrical stewpot was investigated. Four sensory attributes including meaty, fatty, kokumi and off‐flavor were used to evaluate the sensory characteristics of different pork bone soups. Twenty‐nine odor active compounds were identified by direct‐time intensity method of gas chromatography–mass spectrometry/olfactometry (GC–MS/O). Only eleven of them were detected in both traditional clay and commercial electrical stewpots. One of the electrical stewpot samples showed good sensory characteristics compared with other samples and its corresponding heating parameters were as follows: heating rate of 2.419°C/min, constant temperature time of 20 min, low temperature of 80°C and its holding time of 50 min. Correlation analysis between sensory attributes and odor active compounds through Partial Least Squares Regression (PLSR) revealed that hexanal, octanal, 6‐methyl‐5‐hepten‐2‐one, 2‐nonanone, decanal, benzaldehyde, (E)‐2‐nonenal had significant correlation with the sensory attributes. Abstract : Correlation analysis between sensory attributes and odor active compounds through Partial Least Squares Regression revealed that hexanal, octanal, 6‐methyl‐5‐hepten‐2‐one, 2‐nonanone, decanal, benzaldehyde, (E)‐2‐nonenal had significant correlation effect with the sensory attributes.